Applicability of explicit potentially inappropriate medication lists to the Australian context: A systematic review. (13th January 2022) - Lee, Georgie; Lim, Joy‐Francesca; Page, Amy T.; Etherton‐Beer, Christopher; Clifford, Rhonda; Wang, Kate
Abstract: Objectives: To determine i) the similarity of potentially inappropriate medications specified in and between existing explicit lists and ii) the availability in Australia of medications included on existing lists to determine their applicability to the Australian context. Methods: This systematic review identified explicit potentially inappropriate medication lists that were published on EMBASE (1974 – April 2021), MEDLINE (1946 – April 2021) and Elsevier Scopus (2004 – April 2021). The reference lists of seven previously published systematic reviews were also manually reviewed. Lists were included if they were explicit, and the most recent version and the complete list were published in English. Lists based on existing lists were excluded if no new items were added. Potentially inappropriate medications identified on each list were extracted and compared to the medications available on the Australian Register of Therapeutic Goods and Australian Pharmaceutical Benefits Schemes. Results: Thirty‐five explicit published lists were identified. A total of 645 unique potentially inappropriate medications were extracted, of which 416 (64%) were available in Australia and 262 (41%) were subsided by the general Pharmaceutical Benefits Scheme. Applicability of each explicit list ranged from 50–96% according to medications available in Australia and 25‐83% according to medications available under subsidy. Conclusions: Pooling data from different lists may help to identify potentially inappropriate medications that may be applicable to local settings. However, if selecting a list for use in the Australian context, consideration should also be given to the intended purpose and setting for application.